Estado e políticas de gestão financeira para a escola pública: a autonomia da escola no PDDE - SILVA, Luizete Cordovil Ferreira da (Universidade Federal do Pará, 2011)
This research discusses the autonomy of the school in the program Programa Dinheiro Direto na Escola - PDDE. It has as objective to understand which concept of autonomy guides the above mentioned politics of the school financial management and which implications this perspective sends to the management of Brazilian government public schools. This is a documental study. The sources used for the collecting of data were 35 official documents which give directions to the PDDE, made of resolutions, provisory acts, booklets, direction manuals, among other documents. To sustain the analysis, the studies of Vitor Paro (1995); (2001); (2003); Licínio Lima (2000a); (2000b); (2001); (2002), Ângela Martins (2002), João Barroso (2003), and others regarding the autonomy of the school were adopted as referential. The study covered ten years of the program in use, which goes from the year of its implantation (1995) to 2004. This study has as borderline the analysis of the autonomy of the school in the guiding plan. Therefore, it has no intention to show how the issue is lived inside the school, starting with the actions of its members. It is simply a conceptual analysis of the autonomy, which starts from the analysis of the documents that guide dictates the politics. The results reveal that the conception of autonomy that guides the PDDE is a functional and operative one, and it points to three processes in the management of brazilian government public schools: 1- to the re-centralization of the state power in the control of the use of financial recourses of the school; 2- to the introduction of the market perspective in the organization of the work in the school; and 3- to the non-obligation of the state regarding the financing and the rendering of state services in the education units.